Evidence that reduced gray matter volume in psychotic disorder is associated with exposure to environmental risk factors. (30th January 2018) - Frissen, Aleida; van Os, Jim; Peeters, Sanne; Gronenschild, Ed; Marcelis, Machteld; ,
Abstract: The aim of this study was to examine whether cannabis use, childhood trauma and urban upbringing are associated with total gray matter volume (GMV) in individuals with (risk for) psychotic disorder and whether this is sex-specific. T1-weighted MRI scans were acquired from 89 patients with a psychotic disorder, 95 healthy siblings of patients with psychotic disorder and 87 controls. Multilevel random regression analyses were used to examine main effects and interactions between group, sex and environmental factors in models of GMV. The three-way interaction between group, sex and cannabis (χ 2 =12.43, p<0.01), as well as developmental urbanicity (χ 2 = 6.29, p = 0.01) were significant, indicating that cannabis use and developmental urbanicity were associated with lower GMV in the male patient group (cannabis: B= −32.54, p < 0.01; developmental urbanicity: B= −10.23, p=0.03). For childhood trauma, the two-way interaction with group was significant (χ 2 = 5.74, p = 0.02), indicating that childhood trauma was associated with reduced GMV in the patient group (B=−9.79, p=0.01). The findings suggest that reduction of GMV in psychotic disorder may be the outcome of differential sensitivity to environmental risks, particularly in male patients. Highlights: Cannabis was associated with reduced GMV in male patients with psychosis. Childhood urbanicity was related to reduced GMV in male patients with psychosis. Childhood trauma was related to reduced GMV in patients with psychosis, both sexes.